Acoustic Spatial Capture-Recapture (aSCR) and the Cryptic Cape Peninsula Moss Frog Arthroleptella lightfooti - Louw, Marike (Stellenbosch : Stellenbosch University, 2018)
Thesis (MSc)--Stellenbosch University, 2018.